Characterization of Patients With Advanced Pancreatic Cancer and High Serum Interleukin-6 Levels. Issue 5 (July 2015) - Miura, Tomofumi; Mitsunaga, Shuichi; Ikeda, Masafumi; Shimizu, Satoshi; Ohno, Izumi; Takahashi, Hideaki; Furuse, Junji; Inagaki, Masatoshi; Higashi, Sayumi; Kato, Hiroyuki; Terao, Kimio; Ochiai, Atsushi
<x xml:space="preserve">Abstract</x> Objectives High serum level of interleukin 6 (IL-6) is associated with high degree of tumor progression and systemic weakness. Anti–IL-6 therapy possibly improves the deterioration of clinical characteristics in patients with high IL-6 level. However, IL-6–related factors in patients with treatment-naive advanced pancreatic cancer (PC) have not been established. The goal of this study was to identify IL-6–related factors in patients with advanced PC who were scheduled to undergo first-line chemotherapy. Methods Patients with treatment-naive advanced PC were eligible for inclusion in this study. Patients who did not receive first-line chemotherapy were excluded. Serum IL-6 levels and clinical parameters were prospectively recorded. Analyses were performed to identify risk factors for high IL-6 levels. Results Eighty patients were analyzed. IL-6–related factors were advanced age (P < 0.01), the presence of liver metastasis (P < 0.01), the large volume of liver metastasis (P < 0.01), severe fatigue (P = 0.02), high carcinoembryonic antigen levels (P = 0.02), anemia (P < 0.01), and high C-reactive protein levels (P = 0.02) in multivariate analyses. Decreased skeletal muscle mass tended to be associated with high IL-6 levels. Conclusions High serum IL-6 was related to advanced age, the presence of hepatic metastasis, large tumor burden in liver, severe fatigue, high carcinoembryonic antigen, high C-reactive protein, and anemia in patients with treatment-naive advanced PC.